ANALYSIS OF INTERNAL AUDIT IMPLEMENTATION AND ITS IMPACT ON SCHOOL FINANCIAL TRANSPARENCY - Biduri, Sarwenda; Widodo, Heri; Rahmawati, Imelda Dian; Firnata, Tifani Angga (Antis-publisher, 2026)
Objective: This research aims to analyze the implementation of internal audits and their impact on the financial transparency of SMP Muhammadiyah 5 Tulangan. Internal audit is one of the important control mechanisms in ensuring accountability and transparency in the management of educational funds. Method: The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. Results: The research results show that the implementation of internal audits has been carried out systematically through the examination of financial documents, evaluation of expenditure procedures, and reporting to the school and foundation leadership. The implementation of internal audits has a positive impact on the improvement of financial report transparency, administrative orderliness, and increased stakeholder trust. Novelty: This research aims to analyze the implementation of internal audits and their impact on the financial transparency of SMP Muhammadiyah 5 Tulangan.